A fun, active and sociable life on display - Nursing home presentations on Instagram - Carlstedt, Elisabeth (Ageing and Society, 2019)
Swedish nursing homes' use of Instagram has increased vastly in the past few years. Instagram is understood as a means to manage the image they wish to mediate to the public. This article examines what is displayed in the nursing homes' Instagram accounts, and what kind of reality is thereby constructed. The data consist of 338 Instagram images from four nursing homes' Instagram accounts. It is found that nursing home life is primarily depicted on Instagram as active, sociable and fun, with informal, friendly relations between staff and residents, and residents able to continue to live as before, if not better, and to interact with surrounding society. Frailty, boredom, loneliness and death were absent from the data, as were mundane care activities. The article concludes that the presentations in the Instagram accounts challenge the traditional idea of nursing homes as total institutions, and the decline and loss associated with living in such institutions; however, there is a risk that these idyllic presentations conceal the inherent problems of nursing home life.
Keywords: image analysis; Instagram; nursing home; reality construction